Sequential relationship: innovation, exportation and performance, and effect of government subsidy - evidence from emerging economies - Lee, Luda (2017)
This study examines the sequential relationship between a firm’s innovation activity, export intensity and performance in emerging economies. Hypotheses were generated based on this framework, and they also modeled the roles played by government subsidy as moderator. Our hypotheses were tested on a sample that includes Chinese, Indian and Russian manufacturing firms. Results in a sequential model show that (1) innovation activity positively and indirectly affects firm performance through exporting, (2) government subsidy strengthens the positive relationship between export intensity and firm performance in emerging economies. However, although previous studies have theoretically identified that the government has a significant role on the relation between firm innovation and export performance, no empirical evidence could be found through this study. Our findings uphold previous theories that the effort of firms to develop their innovation leads to a firm’s increase of export and profit, and the moderating role of the government substantially affect export intensity in emerging economies.